Pediatric obesity and development of the penis and testis - Danbee Lee; Jae Min Chung; Sang Don Lee (Investigative and Clinical Urology, 2024)
Purpose: Pediatric obesity is increasing in many countries as socioeconomic status improves and the consumption of high calorie food increases. Thus, effect of obesity on genital development is an important topic. This study aimed to determine relationships of body mass index (BMI) with penile parameters and testicular volume in pediatric patients without penile or testicular abnormalities. Materials and Methods: Data from 1,499 male pediatric patients from our center were analyzed. Patients with penile or testicular abnormalities were excluded. Their age ranged from 2 to 18 years. These patients were divided into two groups based on their BMI: normal BMI (5th–85th percentile) and high BMI (≥85th percentile). Factors used in analysis included age, anthropometric indicators, baseline penile length (BPL), stretched penile length (SPL), penile circumference (PC), and mean testicular volume. These same parameters were analyzed for different age groups. Results: Pediatric patients with normal BMI showed longer BPL and SPL than patients with high BMI (p<0.05). However, PC and mean testicular volumes showed no significant difference between the two groups. BPL was significantly longer in the normal BMI group starting at ten years of age. SPL was significantly longer in the normal BMI group starting at eleven years of age. Conclusions: Our study confirms that having a higher BMI during childhood has a negative effect on penile length. However, there was no significant relationship between BMI and PC or testicular volume.